2022
DOI: 10.3390/ani12040506
|View full text |Cite
|
Sign up to set email alerts
|

A Field-Deployable Insulated Isothermal PCR (iiPCR) for the Global Surveillance of Toxoplasma gondii Infection in Cetaceans

Abstract: Toxoplasmosis is a zoonotic disease with veterinary and public health importance worldwide. Toxoplasma gondii infection in cetaceans is an indicator of land-to-sea oocyst pollution. However, there is a critical knowledge gap within the distribution of the T. gondii infection in cetaceans. To facilitate the global surveillance of this important zoonotic pathogen, we developed a field-deployable duplex insulated isothermal PCR (iiPCR) with automated magnetic bead-based DNA extraction for the on-site detection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Cats are not only the definitive host of T. gondii but also excrete the environmentally resistant oocysts in their feces ( 10 ). Millions of T. gondii oocysts can be shed from felids, leading to infection of other susceptible hosts ( 11 ). Meta-analyses over the past 50 years showed that the seroprevalence of T. gondii in domestic and wild felids was around 35% and 59%, respectively ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cats are not only the definitive host of T. gondii but also excrete the environmentally resistant oocysts in their feces ( 10 ). Millions of T. gondii oocysts can be shed from felids, leading to infection of other susceptible hosts ( 11 ). Meta-analyses over the past 50 years showed that the seroprevalence of T. gondii in domestic and wild felids was around 35% and 59%, respectively ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…This technology duplicates the process of in vitro DNA synthesis through enzymatic reaction, may amplify the target gene fragment exponentially, and has the benefits of high sensitivity, good specificity, cheap cost, and fast speed, making it extensively employed in pathogen detection. In less than 40 years since 1985, advanced methods such as nested PCR [ 11 ], multiplex PCR [ 12 ], real-time PCR (qPCR) [ 13 ], droplet digital PCR (ddPCR) [ 14 ], nanoPCR [ 15 ], and insulated isothermal PCR (iiPCR) [ 16 ] have been invented for clinical testing based on following the principles of the technique.…”
Section: Introductionmentioning
confidence: 99%
“…Few cases of protozoan Toxoplasma gondii infection in cetaceans have been documented in several nations in North America, Western Europe, and Oceania. However, there remains a lack of information regarding this infection in certain regions, including Southeastern Asia, South Asia, South America, and Africa (6). However, a study indicated that there is a plausible chance of toxoplasmosis in cetacean populations in the Philippines by detecting 71% of the sampled cetaceans that were infected with T. gondii (7).…”
Section: Introductionmentioning
confidence: 99%